Applied puppetry: Communities, identities, transgressions. Issue 1 (1st July 2020) - Purcell-Gates, Laura; Smith, Matt
This editorial outlines the scope of this special issue on puppetry. The issue editors introduce articles that theorize the use of puppets for a purpose and present dialogues with practitioners working in the field. The authors emphasize the power of puppetry within contemporary cultural systems and the plethora of diverse practices comprising applied puppetry. The lively and developing field of applied puppetry is presented as involving new thinking and methods that have been adopted globally. The editorial argues that applied puppetry, as well as being a set of practices that can affect the lives of participants, is also a robust academic field. The authors hope for a reconsideration of objects in applied theatre practice generally, as a way to further understand networks in socially engaged performance practices.